Showcasing Vällingby to the world: post-war suburban development, informational infrastructures, and the extrospective city. (3rd July 2018) - Cook, Ian R.
ABSTRACT: Vällingby – one of the first post-war suburbs in Stockholm – became a well-known and much visited development, a prominent place in the geographical imaginations of many planners and architects during the 1950s and 1960s. This article will consider the ways in which Vällingby was 'showcased' to planners and architects outside of Sweden during this period. It will demonstrate how this was achieved through three practices in particular: (1) the hosting of visitors to Vällingby; (2) the promotion of Vällingby by those governing and marketing the development; and (3) the reporting of the development in English language planning and architect journals. In so doing, the article will speak to the academic literature on policy mobilities and two important concepts within it: informational infrastructures and the extrospective city.